Feeding Patterns, Nutritional Status of Available Feeds During Advanced Pregnancy and Incidence of Reproductive and Metabolic Disorders in Buffaloes of Indore District of Madhya Pradesh - Thakur, Dinesh; Jain, Ravindra Kumar; Sharma, Pradeep; Yadav, Anil (Indian Journal of Animal Nutrition, 2017)
A survey was conducted on feeding pattern along with usage of mineral mixture, salt and occurrence of common pre and post parturient reproductive and metabolic disorders in 10 villages of Mhow tehsil, Madhya Pradesh, India. Ten-twelve farmers from each village were selected randomly and data were collected on feeding pattern. Samples of feedstuffs from each village were collected and pooled for analysis of proximate constituents, Ca, P and trace minerals. The majority of farmers were using mixture of straws (wheat straw + gram straw) as dry roughage (66%) and local grasses as green roughage (55%) along with wheat bran plus cotton seed cake as concentrate (39%). Only 14% farmers used mineral mixture and 65% farmers used common salt as supplements. Out of 815 buffaloes, uterine prolapse was the most prevalent reproductive disorder (8.71%) followed by retention of placenta (7.48%), vaginal prolapse (6.87%). Haemoglobinuria was the most prevalent metabolic disorders in buffaloes (9.30%) followed by milk fever (6.01%). The prevalence of mastitis (10.04%) was higher than other problems in buffaloes. The CP contents in straws ranged from 3.54 to 6.11%, EE from 0.76 to 1.97%, CF from 37.72 to 45.19%, TA from 8.05 to 12.33% and AIA from 1.48 to 6.97%. Among green roughages, CP varied from 4.29 to 7.00%, EE from 1.14 to 1.48%, TA from 7.95 to 10.69% and AIA from 1.61 to 3.98%. Among concentrates, CP level ranged between 12.53 to 20.97%, EE from 1.47 to 8.58%, CF from 5.86 to 29.61%, TA from 4.96 to 14.77% and AIA from 0.58 to 2.59%. Calcium was deficient in wheat bran and cotton seed cake.Phosphorus was deficient in roughages expect in maize fodder. All feedstuffs were high in iron. Copper was deficient in wheat straw, masoor straw, maize fodder and MP chari. All feeds were deficient in Zn except wheat bran and compounded feeds. Cobalt was adequate in all most all feeds. It could be concluded that the advanced pregnant buffaloes were mostly fed on straw based ration with little green and concentrate without mineral supplementation. The prevalence of mastitis was higher than pre and post parturient reproductive and metabolic disorders. The most of the feedstuffs were deficient in P, Cu and Zn.